2022
DOI: 10.3389/fimmu.2022.876271
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity, Infections, and the Risk of Monoclonal Gammopathy of Undetermined Significance

Abstract: Various epidemiological studies, including case reports and -series in addition to larger, population-based studies, have reported an increased prevalence of monoclonal gammopathy of undetermined significance (MGUS) and multiple myeloma in individuals with a prior history of immune-related conditions. This is believed to support the role of chronic antigen stimulation in the pathogenesis of these conditions. In this short review, we summarize some of the largest population-based studies researching autoimmune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Therefore, it appears that non‐respiratory viruses may interact directly with plasma cells and interfere with their growth and differentiation. In addition, respiratory tract infections have been suspected to be responsible for an increased risk of developing MGUS over time 10,16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it appears that non‐respiratory viruses may interact directly with plasma cells and interfere with their growth and differentiation. In addition, respiratory tract infections have been suspected to be responsible for an increased risk of developing MGUS over time 10,16 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, respiratory tract infections have been suspected to be responsible for an increased risk of developing MGUS over time. 10,16 During COVID-19 the "cytokine storm" (in particular, the secretion of IL-6) promotes the differentiation of B lymphocytes into plasma cells, that physiologically produce immunoglobulins. 24,26 In this view, our data show that there is no significant association between the development of MGUS and the respiratory virus SARS-CoV-2, both during the disease period and at short-term follow-up (3-12 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the myeloma monoclonal (M) Ig itself has autoantibody activity against several tissue antigens including collagen IV, phospholipase A2 receptor, collagen VII, myelin-associated glycoprotein, gangliosides, and lipoproteins, and by forming ICs and activating complement, it induces extensive tissue damage and cytokine secretion ( 71 ). Furthermore, autoimmune patients with detectable autoantibodies are at a significantly increased risk of MGUS than autoantibody-negative patients ( 72 , 73 ). Our results indicate that ICs in MM do not only induce tissue damage as previously reported but also regulate the ECM through induction of FDC–SPARC and modify the expression of several MM-associated oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal gammopathy of undetermined significance (MGUS) is characterized by the presence of a monoclonal paraprotein in the blood, without the characteristic end organ damage seen in multiple myeloma. Numerous studies have found an increased incidence of MGUS in patients with autoimmune diseases, and their treatment may play an important role in the etiology of MGUS ( 27 , 28 ). However, the presence of monoclonal immunoglobulin and APS in the same patient is unusual.…”
Section: Introductionmentioning
confidence: 99%